Efektivitas Penyelesaian Sengketa Ekonomi Syariah Di Pengadilan Agama - Aziz, Muhammad Miftah; Sabiq, Fairuz (STAI Al Musaddadiyah Garut, 2025)
This paper discusses the effectiveness of resolving sharia economic disputes in religious courts. The research problem raised is Since the first time the Religious Court was given the authority to resolve Sharia Economic disputes, many have doubted the effectiveness of resolving sharia economic disputes in religious courts. The purpose of this study is to analyze the effectiveness of resolving sharia economic disputes in religious courts in resolving sharia economic disputes. The writing method used is the normative writing method with a statutory regulatory approach and an analytical approach. The results of this study indicate that the Religious Court does not yet have its own procedural law, even though many cases that are the authority of the Religious Court have their own characteristics that are specific and different from cases in general civil law. The ability of judges in religious courts is the most highlighted since the authority was given to religious courts to resolve sharia economic disputes. So that improvements are needed in terms of strengthening the system and increasing the ability of judges. Keywords: Religious Courts, Disputes, Sharia Economics